Freedom and Compulsion in Personal Behavior - Ramchev, Kolyo (Research Papers, 2016)
The motives behind the choice of this study could be presented in the following way:Topic is significant and of present interest for our society, particularly for its thinking part.Topic is a problem of the hour and debatable. There is a small amount of publications abroad and at home. I have been working for a long period of time on the issues of personality, its behavior, the freedom of its choice and the constraints that limit it.My researcher’s  interest, as well as its realization in this study, is focused on the issue of the freedom of personality. In order to develop the problem for the individual freedom, it was necessary to “pass” through elaboration of the issues ofpersonality, its behaviour and the constraints it experienced, which stem from the society. All this is in the context of the problem for thefreedom of the personality.Writing this study, I have used the deductive approach. In my opinion it is suitable and gives good results. The topic is developed mainly from a psychological and partly from a sociological point of view. I consider this combination to be justified and successful.The main thesis in the study is: “Personality might be free, that it must be free, but it is not free”.The way I have elaborated on my reasoning is not impossibly optimistic, but it is not desperately pessimistic, either. The way I have elaborated on my reasoning, analysis and findings is realistic. At the end of the study it is pointed out that the only alternative to societal constraints on personality is establishing and maintainingdirect democracy!
Keywords: Behavior; Compulsion; Social reactions; Outside compulsions; Inside stops; Desires; Personality; Freedom